Effect of cardanol on the physical and chemical properties of sodium caseinate-coated papers for packaging applications - Jihyeon Hwang; Yeon-Ji Jo; Dowan Kim (Future Foods)
Despite their widespread application in food packaging, petroleum-based plastics contribute toward several environmental problems throughout their life cycle. Paper is considered a sustainable packaging material; however, its poor gas and water-vapor barrier properties limit its application in the food industry. In this study, papers coated with bio-based sodium caseinate (CasNa) and cardanol (CL), a plasticizer, are prepared as a sustainable food packing material. The morphological and chemical structure, mechanical properties, oxygen and water-vapor permeability, and thermal stability of pristine CasNa- and CasNa/CL-coated papers are investigated based on their CL content. CL incorporation into the CasNa matrix disrupts the robust physical interactions of CasNa, increasing the flexibility of CasNa-coated papers. Consequently, with increasing CL content, the hydrophobicity of the CasNa/CL-coated papers is enhanced with a reduction in the water-vapor transmittance rate from 461.3 ± 2.0 to 389.8 ± 3.9 g/m2·day and an increase in the water contact angle from 56.6 ± 2.4° to 72.9 ± 1.1°. Notably, the taste and flavor of coffee packaged with commercial and CasNa/CL (100 %)-coated coffee drip bags are similar, possibly owing to the good gas barrier properties of the CasNa/CL-coated papers. Therefore, this study proposes a bio-based green alternative to petroleum-based plastics that is expected to exhibit wide commercial applicability in packaging. Moreover, the results of this study could open new frontiers in sustainable food packaging.